Enforcing International Trade Agreements with Imperfect Private Monitoring - Park, Jee-Hyeong (Review of Economic Studies, 2011)
To analyse the role that the World Trade Organization (WTO) plays in enforcing international trade agreements, this paper first explores what countries can achieve alone by characterizing optimal private trigger strategies ( PTS ) under which each country triggers a punishment phase by imposing an explicit tariff based on privately observed imperfect signals of the other country's concealed trade barriers. It identifies the condition under which countries can restrain the use of concealed barriers based on PTS and establishes that countries will not reduce the cooperative protection level to its minimum attainable level under the optimal PTS . This paper then considers third-party trigger strategies ( TTS ) under which the WTO allows each country to initiate a punishment phase based on the WTO's judgement about potential violations. By comparing the optimal PTS and optimal TTS , it demonstrates that the WTO facilitates a better cooperative equilibrium by changing the nature of punishment-triggering signals from private to public , which in turn enables countries to use a more efficient punishment, such as an asymmetric and a minimum punishment.